Comparative efficacy evaluation for various anticonvulsant drugs to restraint epileptiform states in rats - R. G. Paronikyan; R. Sh. Sargsyan; J. S. Sarkissyan; G. G. Avakyan; V. M. Avakyan; V. R. Sargsyan; A. V. Margaryan (Эпилепсия и пароксизмальные состояния, 2025)
Objective: development of a simple algorithm to comparatively evaluate effectiveness of various anticonvulsant drugs (ACDs) for restraining epileptiform states in rats.Material and methods. The experiments were conducted with 120 white male rats weighing 180–220 g. Using Bioscope hardware complex, the standard indicators of animals’ condition were assessed after injection of various ACDs and after corazole was subcutaneously administered in ACD-treated rats. For a quantitative assessment of the animals’ condition, a spectrum of the original Bioscope signals was constructed to determine interpeak intervals of the oscillatory signals, calculate 16 statistical indicators for a set of successive interpeak intervals followed by constructing their spectrum.Results. An algorithm based on analyzed bioscopic indicators of the animals’ condition was proposed. It was shown that lamotrigine at a dose of 25 mg/kg did not restrain convulsive states after corazole administration, and its conditional effectiveness score was zero. However, after increasing the dose of lamotrigine to 70 mg/kg, its total effectiveness score reached 3. The use of topiramate at a dose of 15 mg/kg turned out to be very effective (maximal 6 points). The high efficiency of using classical drugs luminal and diazepam for restraining convulsive states (6 and 5 points, respectively) was also noted.Conclusion. The proposed analytical methodology is functional and allows identifying ACDs that can be used most effectively to relieve body epileptiform conditions.